Odpowiedzi

2009-12-27T18:16:06+01:00
-3=-2a+b /:(-1)
3=a+b

3=2a-b
3=a+b

6=3a/:3
a=2
b=3-a=3-2=1

równanie prostej:
y=2x+1

:)
2009-12-27T18:16:42+01:00
A(-2,-3)
B(1,3)

musimy podstawić x i y do ogolnego rownania prostej: y=ax+b i rozwiazac uklad rownan:

-3=a* (-2) +b
3= a * 1 + b

-3=-2a+b
3=a+b

a=3-b
-3=-2*(3-b)+b

-3=-6+2b+b
3=3b
b=1

a=3-b
a=2

i podstawiamy:
y=2x+1
2009-12-27T20:06:44+01:00
Zad.
-3=-2a+b
3=a+b /(-1)

-3=-2a+b
-3=-a-b

-6=-3a / (-3)
a= 2

3=2+b
3-2=b
1=b
a=2

Wzór funkcji to:
y= 2x+1